LncRNAs regulate ferroptosis to affect diabetes and its complications - Chen, Qianqian; Ji, Hao; Lin, Yue; Chen, Zheyan; Liu, Yinai; Jin, Libo; Peng, Renyi (Frontiers in Physiology, 2022)
Worldwide, the rapid increase in the incidence of diabetes and its complications poses a serious threat to human health. Ferroptosis, which is a new nonapoptotic form of cell death, has been proven to be closely related to the occurrence and development of diabetes and its complications. In recent years, lncRNAs have been confirmed to be involved in the occurrence and development of diabetes and play an important role in regulating ferroptosis. An increasing number of studies have shown that lncRNAs can affect the occurrence and development of diabetes and its complications by regulating ferroptosis. Therefore, lncRNAs have great potential as therapeutic targets for regulating ferroptosis-mediated diabetes and its complications. This paper reviewed the potential impact and regulatory mechanism of ferroptosis on diabetes and its complications, focusing on the effects of lncRNAs on the occurrence and development of ferroptosis-mediated diabetes and its complications and the regulation of ferroptosis-inducing ROS, the key ferroptosis regulator Nrf2 and the NF-κB signaling pathway to provide new therapeutic strategies for the development of lncRNA-regulated ferroptosis-targeted drugs to treat diabetes.